Changes in the Quality Attributes of Edible Vegetable Oils During Deep Frying Concerning Defence Ration - Yadav, Dev Kumar; Kadam, Prathamesh; Wadikar, DD.; Vignesh, Kannan; Semwal, A.D. (Defence Life Science Journal, 2023)
Deep fat frying is a popular cooking method that can significantly alter the physico-chemical properties of edible oils. This unit operation is very common both in civil as well as institutional level training, recreational and feeding centres owing to the high liking of fried products among all age groups. Frying is a high-temperature process where food material is normally exposed to longer periods depending upon its moisture content and results in the desirable colour, aroma and taste that is most acceptable to the consumers. But the quality of oil changes each after the frying cycle and leads to the onset of various physicochemical changes resulting in the accumulation of toxic compounds that may pose potential health risks. Various edible oils from plant sources have varied stability against high-temperature exposure, hence, the selection of appropriate edible vegetable oils for deep frying is critical to ensure its safety during repeated use. The current article summarizes the available literature on the changes in quality attributes of edible vegetable oils during deep frying along with the mechanisms of oil degradation, including oxidation and hydrolysis, formation of trans fats, and major concerns during deep frying. This also covers various methods of assessing the quality of frying oils, inclusive of measurement of free fatty acids, peroxide value, polar compounds, and oxidative stability. The impact of deep frying on the nutritional value of edible vegetable oils, such as changes in fatty acid composition, effects of different frying conditions, such as temperature and time, on the quality of the frying oil and the loss of antioxidant compounds is also discussed rationally The facts and finding covered under present manuscript will be useful to food manufacturers and consumers in selecting appropriate edible vegetable oils for deep frying, maintaining the desired food quality, and ensuring the safety of various edible oils and their blends concerning both civil and the Defence supplies.